2022
DOI: 10.1073/pnas.2113329119
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally distinct CD4+Treglineages shape the CD8+T cell response to acuteListeriainfection

Abstract: Significance The CD4 + T reg response following acute Listeria infection is heterogeneous and deploys two distinct modes of suppression coinciding with initial pathogen exposure and resolution of infection. This bimodal suppression of CD8 + T cells during priming and contraction is mediated by separate T reg lineages. These findings make a significant contribution to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In PNAS, Dolina et al. ( 8 ) demonstrate that distinct Treg cell populations arise during acute Listeria monocytogenes ( Lm ) infection, with discrete effects at regulating CD8 + T cell responses during the priming versus contraction phases ( Fig. 1 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In PNAS, Dolina et al. ( 8 ) demonstrate that distinct Treg cell populations arise during acute Listeria monocytogenes ( Lm ) infection, with discrete effects at regulating CD8 + T cell responses during the priming versus contraction phases ( Fig. 1 ).…”
mentioning
confidence: 99%
“…To investigate the role of Treg cells in regulating the adaptive immune response against acute infection, Dolina et al. ( 8 ) infected C57BL/6 mice with Lm Δ actA -Ova (an attenuated Listeria strain with deletion of the virulence factor actA and expression of chicken ovalbumin [Ova]), which could induce distinct Treg responses according to low or high dose of bacterial challenge ( 10 ). They found that there were two distinct waves of Treg cell responses that occurred at days 1 and 7 after Listeria infection (called day 1 and day 7 Treg cells, respectively).…”
mentioning
confidence: 99%
See 3 more Smart Citations